Asiatic Acid Exhibits Anti-inflammatory and Antioxidant Activities against Lipopolysaccharide and d-Galactosamine-Induced Fulminant Hepatic Failure - Lv, Hongming; Qi, Zhimin; Wang, Sisi; Feng, Haihua; Deng, Xuming; Ci, Xinxin (Frontiers in Immunology, 2017)
Inflammation and oxidative stress are essential for the pathogenesis of fulminant hepatic failure (FHF). Asiatic acid (AA), which is a pentacyclic triterpene that widely occurs in various vegetables and fruits, has been reported to possess antioxidant and anti-inflammatory properties. In this study, we investigated the protective effects of AA against lipopolysaccharide (LPS) and d-galactosamine (GalN)-induced FHF and the underlying molecular mechanisms. Our findings suggested that AA treatment effectively protected against LPS/d-GalN-induced FHF by lessening the lethality; decreasing the alanine transaminase and aspartate aminotransferase levels, interleukin (IL)-1β, IL-6, and tumor necrosis factor-α production, malondialdehyde formation, myeloperoxidase level and reactive oxygen species generation (i.e., H2O2, NO, and O2−), and increasing the glutathione and superoxide dismutase contents. Moreover, AA treatment significantly inhibited mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathway activation via the partial induction of programmed cell death 4 (PDCD4) protein expressions, which are involved in inflammatory responses. Furthermore, AA treatment dramatically induced the expression of the glutamate-cysteine ligase modifier subunit, the glutamate-cysteine ligase catalytic subunit, heme oxygenase-1, and NAD (P) H: quinoneoxidoreductase 1 (NQO1), which are largely dependent on activation of the nuclear factor-erythroid 2-related factor 2 (Nrf2) through the induction of AMP-activated protein kinase (AMPK) and glycogen synthase kinase-3β (GSK3β) phosphorylation. Accordingly, AA exhibited protective roles against LPS/d-GalN-induced FHF by inhibiting oxidative stress and inflammation. The underlying mechanism may be associated with the inhibition of MAPK and NF-κB activation via the partial induction of PDCD4 and upregulation of Nrf2 in an AMPK/GSK3β pathway activation-dependent manner.